The ownership and control architecture of South Africa's state-owned companies and its impact on corporate governance - Thabane, Tebello (Department of Commercial Law, 2021)
The thesis examines the ownership model and various control arrangements of state-owned companies (SOCs) to establish how the division of corporate power between the boards of directors and shareholder-representatives and the exercise of corporate power by these organs impact corporate governance. The thesis makes several claims. First, it argues that the architecture of ownership and control is not underpinned by a sound theoretical base and lacks a clear and consistent economic and political logic. Second, the motivations for state ownership are vague and contradictory, resulting in an irrationally amorphous ownership model. Third, shareholder control powers are excessive, often abused, and lead to shareholder proximity to the locus of governance, which engenders interference and erodes boards' autonomy and authority to govern effectively. Fourth, the legal and regulatory regime governing SOCs is plural, complex, fragmented, and contradictory. Collectively, these and other conceptual flaws have an adverse impact on governance. To address the flaws, the true nature and role of SOCs as entities of a special kind designed to fulfil an overarching public interest mandate need to be reimagined. To realise the public interest mandate, SOCs must be governed in the public interest. This has several aspects. The first is the truncation of excessive shareholder powers and the elimination of interference by removing SOCs from direct political control and placing them under an independent and professional shareholder entity akin to Singapore's state holding company, Temasek. The second aspect is a rethink and expansion of the duties of SOCs' directors by introducing a novel duty to act in the public interest, in addition to their traditional duties. The third aspect is that the legal and regulatory framework must be de-layered, responsive, and complementary to accommodate and give impetus to the public interest approach to corporate governance. Ultimately, these changes must culminate in a nuanced and bespoke architecture of ownership and control that is minimalist and structured and that can, arguably, address the idiosyncratic governance challenges that confront South African SOCs.